How can we explain the frontal presentation of insular lobe epilepsy? The impact of non-linear analysis of insular seizures. Issue 5 (May 2017) - Hagiwara, Koichi; Jung, Julien; Bouet, Romain; Abdallah, Chifaou; Guénot, Marc; Garcia-Larrea, Luis; Mauguière, François; Rheims, Sylvain; Isnard, Jean
Highlights: Non-linear regression analysis was applied to insular seizures with/without frontal presentation. Seizures propagation to the mesial frontal/cingulate regions is common in insular lobe epilepsy. Frontal presentation is mediated by strong functional coupling to the mesial frontal regions. Abstract: Objective: For a decade it has been known that the insular lobe epilepsy can mimic frontal lobe epilepsy. We aimed to clarify the pattern of functional coupling occurring during the frontal presentation. Methods: We analyzed five insular lobe epilepsy patients. Frontal semiology was predominant for three of them, whereas insular semiology was predominant for the two others. We applied the non-linear regression analysis to stereoelectroencephalography-recorded seizures. A directed functional coupling index was calculated during clonic discharge periods that were accompanied either with frontal or insular semiology. Results: We found significant functional coupling between the insula and mesial frontal/cingulate regions, with the former being a leader region for seizures propagation. Extra-insular regions showed significantly less or even no coupling with the mesial hemispheric regions. The three patients with frontal semiology showed strong couplings with the mesial frontal as well as cingulate regions, including the medial orbitofrontal cortex, pre-SMA/SMA, and the anterior to posterior cingulate. The two patients with the insular semiology only showed couplings between the insula and cingulate regions. Conclusions: The frontal semiology was expressed by strong functional couplings between the insula and mesial frontal regions. Significance: The insular origin of seizure should be considered in cryptogenic mesial frontal epilepsies.